Non-pharmacological interventions for self-management of fatigue in adults: an umbrella review of potential interventions to support patients recovering from critical illness - Brown, SE; Shah, A; Czuber-Dochan, W; Bench, S; Stayt, L (Elsevier, 2023)
Purpose: Fatigue is a common symptom after critical illness. However, evidence-based interventions for fatigue after critical illness are lacking. We aimed to identify interventions to support self-management of fatigue caused by physical conditions and assess their effectiveness and suitability for adaptation for those with fatigue after critical illness.